منهج الإمام فخر الدين الرازي في تفسيره للآيات الكونية: دراسة تحليلية - سيوطي، سيف السبحان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study investigates the methodology of Imam Fakhr al-Din al-Razi in his book “Mafatiḥ al-Ghayb” towards the cosmic verses (al-Ayat al-Kauniyyah) in the Qur'an. Imam Fakhr was particularly interested in verses which refer to the signs that appear in the heavens and earth that re-affirm the existence of Allah swt and the truthfulness of His Messenger Prophet Muhammad (pbuh). The interpretations were examined critically between al-Razi's scientific interpretation and the discoveries of modern sciences. The study was conducted using library research by collecting primary and secondary resources to obtain the necessary data and to analyze them critically. The findings indicate that al-Razi had applied a new method of interpretation which had never been used before by and other commentators. He made use, extensively, rational sciences on top of transmitted sciences. His interpretation of these verses was influenced by what al-Ghazali (505 AH) wrote in his books such as The Jewels of the Qur'an and Reviving the Religious Sciences.